2012
DOI: 10.1111/gbb.12003
|View full text |Cite
|
Sign up to set email alerts
|

Dense‐map genome scan for dyslexia supports loci at 4q13, 16p12, 17q22; suggests novel locus at 7q36

Abstract: Analysis of genetic linkage to dyslexia was performed using 133,165 array-based SNPs genotyped in 718 persons from 101 dyslexia-affected families. Results showed five linkage peaks with lod scores >2.3 (4q13.1, 7q36.1-q36.2, 7q36.3, 16p12.1, and 17q22). Of these five regions, three have been previously implicated in dyslexia (4q13.1, 16p12.1, and 17q22), three have been implicated in attention-deficit hyperactivity disorder (ADHD, which highly co-occurs with dyslexia; 4q13.1, 7q36.3, 16p12.1) and four have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 76 publications
2
49
0
Order By: Relevance
“…Field et al 2013, performed a joint linkage and association study on 718 individuals from 101 dyslexia families with 100,000 SNPs. Again, they did not find any associations that met the threshold of genome-wide significance (1 × 10 −8 [96]) [97]. They did however, find suggestive association ( p = 6.2 × 10 −7 ) with an SNP 77 Kb downstream of the FGF18 gene, which has been implicated in lateralization [97].…”
Section: Gwa Studies Of Speech and Language-related Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Field et al 2013, performed a joint linkage and association study on 718 individuals from 101 dyslexia families with 100,000 SNPs. Again, they did not find any associations that met the threshold of genome-wide significance (1 × 10 −8 [96]) [97]. They did however, find suggestive association ( p = 6.2 × 10 −7 ) with an SNP 77 Kb downstream of the FGF18 gene, which has been implicated in lateralization [97].…”
Section: Gwa Studies Of Speech and Language-related Traitsmentioning
confidence: 99%
“…Again, they did not find any associations that met the threshold of genome-wide significance (1 × 10 −8 [96]) [97]. They did however, find suggestive association ( p = 6.2 × 10 −7 ) with an SNP 77 Kb downstream of the FGF18 gene, which has been implicated in lateralization [97]. Luciano et al reported a meta-analysis of quantitative reading and language measures across two relatively large population-based samples (1177 individuals from 538 families and approximately 5000 cases) [98].…”
Section: Gwa Studies Of Speech and Language-related Traitsmentioning
confidence: 99%
“…Genotyping was performed on 36 PBC affected persons and 27 unaffected relatives from 27 affected families. Individuals were genotyped for 262 217 single nucleotide polymorphisms (SNPs) on the NspI array from the Affymetrix Human Mapping 500K Array Set using an Affymetrix GeneChip ® Instrument System, as previously described . There were 10 families that were informative for linkage.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, novel loci of interest have recently been suggested by new linkage screens and the first GWAS in SLI, dyslexia and general population cohorts, and replication should be sought for these loci (Bartlett et al 2014;Field et al 2013;Nudel et al 2014;Luciano et al 2013;Harlaar et al 2014;Gialluisi et al 2014). These studies have highlighted the absence of single common variants of large effect on language-related phenotypes.…”
Section: Stutteringmentioning
confidence: 99%